UJI AKTIVITAS ANTIBAKTERI EKSTRAK BUNGA KECOMBRANG (Etlingera elatior) TERHADAP PERTUMBUHAN BAKTERI Salmonella thypi - Nasution, Pandapotan; Marpaung, Jon Kenedy; Suharyanisa, Suharyanisa; Sitanggang, Rolastri (UNIVERSITAS SARI MUTIARA INDONESIA, 2022)
Kecombrang (Etlingera elatior) is a type of spice that has long been known and used by humans as medicine. Kecombrang flower parts contain several chemical compounds, namely: alkaloids, flavonoids, and saponins. In addition, kecombrang flowers can also inhibit the growth of Salmonella typhi bacteria. This study aims to determine the concentration of ethanolic extract of kecombrang flower (Etlingera elatior) which is effective in inhibiting the growth of Salmonella typhi bacteria. The research sample was Kecombrang Flowers purchased at the Tarutung traditional market. This research was carried out experimentally including sampling, drying simplicia, maceration using 70% ethanol solvent, making extracts made using a rotary evaporator, and testing the antibacterial activity of kecombrang flowers using the disc diffusion method. Data analysis was conducted to see the effect of kecombrang flower ethanol extract on the activity of Salmonella typhi bacteria. The results of the study found that the results of phytochemical screening showed simplicia and ethanol extract of kecombrang flower leaves contained alkaloids, flavonoids, and saponins. While the results of the antibacterial activity test of the ethanolic extract of kecombrang flower leaves have antibacterial properties against Salmonella typhi at extract concentrations of 45%, 50%, 55%, and 60% with inhibition zone diameters of 9.4 mm, 12.2 mm, 14.8 mm, respectively. , 16.3mm. The most effective concentration of ethanol extract to inhibit the growth of Salmonella typhi was at a concentration of 60% with a larger inhibition zone diameter of 16.3 mm.